Surgery-Induced Hippocampal Angiotensin II Elevation Causes Blood-Brain Barrier Disruption via MMP/TIMP in Aged Rats - Li, Zhengqian; Mo, Na; Li, Lunxu; Cao, Yiyun; Wang, Wenming; Liang, Yaoxian; Deng, Hui; Xing, Rui; Yang, Lin; Ni, Cheng; Chui, Dehua; Guo, Xiangyang (Frontiers in Cellular Neuroscience, 2016)
Reversible BBB disruption has been uniformly reported in several animal models of postoperative cognitive dysfunction (POCD). Nevertheless, the precise mechanism underlying this occurrence remains unclear. Using an aged rat model of POCD, we investigated the dynamic changes in expression of molecules involved in BBB disintegration, matrix metalloproteinase-2 (MMP-2) and -9 (MMP-9), as well as three of their endogenous tissue inhibitors (TIMP-1, -2, -3), and tried to establish the correlation between MMP/TIMP balance and surgery-induced hippocampal BBB disruption. We validated the increased hippocampal expression of angiotensin II (Ang II) and Ang II receptor type 1 (AT1) after surgery. We also found MMP/TIMP imbalance as early as 6 h after surgery, together with increased BBB permeability and decreased expression of Occludin and zonula occludens-1 (ZO-1), as well as increased basal lamina protein laminin at 24 h postsurgery. The AT1 antagonist candesartan restored MMP/TIMP equilibrium and modulated expression of Occludin and laminin, but not ZO-1, thereby improving BBB permeability. These events were accompanied by suppression of the surgery-induced canonical nuclear factor-κB (NF-κB) activation cascade. Nevertheless, AT1 antagonism did not affect nuclear receptor peroxisome proliferator-activated receptor-γ expression. Collectively, these findings suggest that surgery-induced Ang II release impairs BBB integrity by activating NF-κB signaling and disrupting downstream MMP/TIMP balance via AT1 receptor.